2021
DOI: 10.1021/acssuschemeng.0c09240
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Mesoporous Sodalite and Graphene Oxide Hybrid Sodalite Using Lithium Silica Fume Waste

Abstract: Mesoporous zeolite and hybrid zeolite are indispensable materials for the chemical industry; however, their fabrication always involved high production cost, long times, and adverse environmental impact. Here, we report a vacuum− ultraviolet (VUV)-initiated reactive oxygen species (ROS) route for the green and fast synthesis of mesoporous sodalite (SOD) zeolite and a hybrid SOD zeolite directly from lithium silica fume (LSF) waste without template. The fast synthesis is based on in situ generation of ROS (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Zeolites, a class of crystalline solid materials with regular microporous frameworks, are widely used in various environmental processes ranging from the adsorptive removal of heavy metal ions and organic pollutants in aqueous media, the catalytic abatement of gaseous emissions in automotive exhausts, to the capture and conversion of greenhouse gases (e.g., CO 2 and CH 4 ). The synthesis of zeolites, however, often needs tedious hydrothermal crystallization processes using expensive organic structure-directing agents (OSDAs), most commonly organic amines, as templates, which are normally added in an excess amount to ensure a high zeolite yield. As a typical example, the small-pore chabazite (CHA) zeolite SSZ-13, which is being utilized as the state-of-the-art catalyst (after introducing Cu ions into the zeolite framework) in diesel exhaust after-treatment systems to eliminate the harmful nitrogen oxides (NO x ) and in the selective methane-to-methanol oxidation, ,, is synthesized using the high-cost N , N , N -trimethyl-1-ammonium adamantine hydroxide (TMAdaOH) as OSDA. After collection and separation of zeolite products, the unreacted OSDAs are discharged as organic pollutants in the wastewater, which not only leads to a waste of the high-value OSDA materials but also requires additional costs for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites, a class of crystalline solid materials with regular microporous frameworks, are widely used in various environmental processes ranging from the adsorptive removal of heavy metal ions and organic pollutants in aqueous media, the catalytic abatement of gaseous emissions in automotive exhausts, to the capture and conversion of greenhouse gases (e.g., CO 2 and CH 4 ). The synthesis of zeolites, however, often needs tedious hydrothermal crystallization processes using expensive organic structure-directing agents (OSDAs), most commonly organic amines, as templates, which are normally added in an excess amount to ensure a high zeolite yield. As a typical example, the small-pore chabazite (CHA) zeolite SSZ-13, which is being utilized as the state-of-the-art catalyst (after introducing Cu ions into the zeolite framework) in diesel exhaust after-treatment systems to eliminate the harmful nitrogen oxides (NO x ) and in the selective methane-to-methanol oxidation, ,, is synthesized using the high-cost N , N , N -trimethyl-1-ammonium adamantine hydroxide (TMAdaOH) as OSDA. After collection and separation of zeolite products, the unreacted OSDAs are discharged as organic pollutants in the wastewater, which not only leads to a waste of the high-value OSDA materials but also requires additional costs for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The increased k f value indicated that external mass transfer of BPs in S-CTF-1 was enhanced by S-doping originating from formation of slight compaction and wrinkling. HSDM described the diffusion process of adsorbates from external surfaces to final internal adsorption sites along the pore surface of CTFs . The D s for BPs adsorption onto CTFs can be determined using Excel Solver through the error minimization method.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that different pore structures can be created to adjust the growth of a range of materials, such as zeolites. Silicalite zeolite, having slit-like mesopores (size of 2.0 to 2.5 nm), has also been developed by the addition of graphene oxide nanosheets throughout the synthesis and subsequent calcination of synthesized samples. Cationic polyelectrolyte functionalized GO was synthesized by the hard template method via incorporation of poly­(diallyl dimethylammonium chloride) (PDDA) into GO, which leads to the formation of slit-like mesopores throughout both sides of the GO surface. The synthesized nanoporous zeolite-Y and zeolite-Y/GO nanocomposites were then examined for their water adsorption capacity. …”
Section: Challenges and Perspectivesmentioning
confidence: 99%